New Treatments (MSC) in Immune Disorders Like Cancers and Covid Infection: Cancer and Virus New Treatment (MSC ) - Ghasemi Darestani, Nadia; Hashemi, Soheyla; Rahimi, Zahra; Janghorbanian Poodeh, Raheleh (Asian Pacific Journal of Cancer Biology, 2024)
The recent coronavirus disease 2019 outbreak and viral infections around the world has had an enormous impact on the global health burden, threatening the lives of many individuals, spatially with underlying disease like cancerous patients and has had severe socio-economic consequences. Many pharmaceutical and biotechnology companies have commenced intensive research on different therapeutic strategies, from repurposed antiviral drugs to vaccines and monoclonal antibodies to prevent the spread of the disease and treat infected patients. Among the various strategies, advanced therapeutic approaches including cell- and gene-editing-based therapeutics are also being investigated, and initial results in in-vitro and early phase I studies have been promising. However, further assessments are required. This article reviews the underlying mechanisms for the pathogenesis of, and discusses available therapeutic candidates and advanced modalities that are being evaluated and used for treatment for immune deficient patients in cancers and viruses infected.